2020
DOI: 10.1007/978-3-030-45002-1_2
|View full text |Cite
|
Sign up to set email alerts
|

An e-Government Implementation Framework: A Developing Country Case Study

Abstract: The implementation of Information and Communication Technology (ICT) is seen globally as a means to efficient and effective delivery of business and organisational mandates. Governments, in their quest to serve citizens, harness ICT to streamline their service delivery processes. e-Government transforms administrations into "smart governments" enhancing the social, political and economic inclusion and the quality of life of its citizens. However, the governments of developing countries are still facing challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…As for research studies conducted in developing countries, it has been found by Basu (2004) that in developing countries information technology plays an important role in the success of e-government and thus reducing the existing digital divide there. While in another study conducted by Apleni and Smuts (2020), it concluded that the governments of developing countries still face some obstacles related to the success of e-government. Also, a study was done by Odat (2012) ascertain the concept followed by the previous researchers in this field, by concluding that there are some issues that must be taken into consideration for the success of the e-government system in developing countries, including the Middle East countries and, perhaps, the most important of them is the infrastructure for information technology and resources (Table 1).…”
Section: Models and Measurement Indicators Proposed (Research Model) For Egovernment System Successmentioning
confidence: 96%
“…As for research studies conducted in developing countries, it has been found by Basu (2004) that in developing countries information technology plays an important role in the success of e-government and thus reducing the existing digital divide there. While in another study conducted by Apleni and Smuts (2020), it concluded that the governments of developing countries still face some obstacles related to the success of e-government. Also, a study was done by Odat (2012) ascertain the concept followed by the previous researchers in this field, by concluding that there are some issues that must be taken into consideration for the success of the e-government system in developing countries, including the Middle East countries and, perhaps, the most important of them is the infrastructure for information technology and resources (Table 1).…”
Section: Models and Measurement Indicators Proposed (Research Model) For Egovernment System Successmentioning
confidence: 96%
“…Empirical findings from several studies highlight how e-government projects have not been supported by, as a Malawian study describes, appropriate "administrative structure, processes, decisionmaking structures, or procedures" and are therefore in conflict with "the way people work" leading to low levels of adoption and motivation to use (Ziba and Kang, 2020: 369-370). In response, much of the focus tends to be on top-down responses that can bring civil servants into line with the platformdesigned processes; such as through executive mandates and strategies (Apleni and Smuts, 2020;Mensah et al, 2021;Ziba and Kang, 2020), as well as by enforcing standards and standard operating procedures (Kang'a et al, 2016: 680).…”
Section: Working Practicesmentioning
confidence: 99%
“…From Liberia to Egypt and South Africa, government officials and researchers have called for greater levels of integration and collaboration to enable more flexible deployment and orchestration of digital services across agencies and departments, and to provide citizens with a more seamless and userfriendly experience (Apleni and Smuts, 2020;Mensah et al, 2021;Reddick et al, 2011). As an example from Lagos State in Nigeria, Olumoye and Govender (2018) aim to address the "separatism of public services" (2018: 2) in the issuing of building development permitswhich normally involves endless backward and forward travel between multiple departments and agencies.…”
Section: Data Integration To Enable Aimentioning
confidence: 99%
“…Perceived ICT infrastructure is one of the top success factors for egovernment in developing countries (Apleni & Smuts, 2020). It is proven by the test results that ICT infrastructure has a positive relationship with e-government implementation (Dahwan & Raju, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Politics is also a combined factor in influencing e-government (Apleni & Smuts, 2020). However, the political contribution in e-government performance reports is still low (Stier, 2015).…”
Section: Introductionmentioning
confidence: 99%